2020
DOI: 10.1038/s41598-020-78099-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome markers and risk of hyperglycemia in pregnancy: a cross-sectional cohort study

Abstract: The aim was to assess the role of Metabolic Syndrome (MetS) diagnostic markers, recommended by three different guidelines, in the prediction of hyperglycemia in pregnancy. This cross-sectional cohort study included 506 non-diabetic women, with a singleton pregnancy, who underwent a diagnostic test for hyperglycemia at 24–28 weeks. Clinical, anthropometric, and laboratory data were obtained. The relationship between MetS markers and the risk of hyperglycemia was evaluated by backward stepwise logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several other studies that evaluated individual metabolic parameters in early pregnancy, with pregnancy outcomes showing that early pregnancy hypertriglyceridemia is significantly associated with GDM [ 24 , 40 , 43 , 46 , 47 ] as well as hypertensive disorders in pregnancy [ 43 , 46 , 48 ]. Another recent study in Brazil showed high TG, WC, FPG, and BP act as independent risk factors for hyperglycaemia in pregnancy [ 49 ]. In this particular population, T2 GDM/DM incidence was not evident among those who already had T1 MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies that evaluated individual metabolic parameters in early pregnancy, with pregnancy outcomes showing that early pregnancy hypertriglyceridemia is significantly associated with GDM [ 24 , 40 , 43 , 46 , 47 ] as well as hypertensive disorders in pregnancy [ 43 , 46 , 48 ]. Another recent study in Brazil showed high TG, WC, FPG, and BP act as independent risk factors for hyperglycaemia in pregnancy [ 49 ]. In this particular population, T2 GDM/DM incidence was not evident among those who already had T1 MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is the potential impact of differences in the metabolic profiles of patients with and without GDM, and the incidence of metabolic syndrome (MetS) among them. MetS is a cluster of cardiovascular disease risk factors, including obesity, atherogenic dyslipidemia, raised blood pressure, insulin resistance, and pro-inflammatory states; although, there are several definitions and cut-points to describe and characterize MetS [ 49 , 50 ]. Women with MetS are at an increased risk of both PE and GDM [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%